The impact of live streaming commerce to MSMES' performance: a comparision between Tiktok and Facebook - Low, Pei Yu (2023)
With the development of technology, live streaming has covered various industries, such as the education industry, the entertainment industry and so on. Thus, this study focused on the new emerging technology for shopping, which is live streaming commerce. This is because there is an empirical gap in the live streaming industry and MSMEs in other countries show low participation in using live streaming commerce, except China. To fill up this gap, this study aimed to investigate the impact of live streaming commerce to MSMEs’ performance and determine the difference between live streaming commerce on TikTok and Facebook. Moreover, the variables including performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, trust, using of live streaming and firm performance have been tested in this study based on the UTAUT2 theory. Qualitative analysis has been conducted in this study to collect 385 sample size. In addition, the SMARTPLS has been used to analyse the reliability, correlation and Structural Equation Modeling of the variables and SPSS has been used to determine the difference between live streaming commerce on TikTok and Facebook. After analysing the data, this research has identified that the firm performance has been influenced by performance expectancy, effort expectancy and trust when using live streaming commerce and the result has been shown in the study as well. Besides, the study has stated the reasons why social influence, facilitating conditions and hedonic motivation have not a significant impact on using live streaming. This study may contribute to future academics who will conduct in this field and gain a deeper insight into the impact of live streaming commerce to MSMEs’ performance.